Two-dimensional perovskite vertical orientation growth solar cell and preparation method thereof
By using the rough surface of tin dioxide nanoparticles in the electron transport layer of perovskite solar cells, the vertical orientation growth of two-dimensional and three-dimensional perovskites is promoted, and the problem of performance degradation of perovskite solar cells under long-term exposure conditions is solved, achieving efficient photoelectric conversion and stable device performance.
Patent Information
- Application Number
- CN202411990400.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-31
AI Technical Summary
Perovskite solar cells tend to degrade their performance under long-term exposure to moisture, light and thermal conditions, and inconsistent crystal orientation in the two-dimensional/three-dimensional composite structure hinders carrier transport.
By using the rough surface of tin dioxide nanoparticles in the electron transport layer, the vertical orientation growth of 2D and 3D perovskites is promoted, forming a highly ordered crystal structure, and the scattering and trapping light effect is enhanced through the partially embedded tin dioxide nanoparticle structure.
It significantly reduces the number of grain boundaries, improves the diffusion length and migration efficiency of carriers, improves the photoelectric conversion efficiency, and enhances the long-term stability and environmental tolerance of the device.
Smart Images

Figure CN119767927A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of perovskite solar cells, and specifically relates to a two-dimensional perovskite vertically oriented growth solar cell and a preparation method thereof. Background Art
[0002] In recent years, perovskite solar cells have become a hot topic in photovoltaic technology research due to their high photoelectric conversion efficiency, low-cost preparation process and great potential in the photovoltaic field. As a representative of the new generation of photovoltaic technology, perovskite solar cells have achieved a certified photoelectric conversion efficiency of more than 26% in the laboratory for single-junction cells due to their excellent light absorption performance, low defect density and excellent carrier transport capacity. However, the stability of perovskite materials remains the main bottleneck for their further promotion and application, especially under long-term exposure to moisture, light and heat conditions, the performance of perovskite solar cells is prone to degradation. Therefore, how to balance the efficiency and stability of perovskite solar cells is an important challenge in current research.
[0003] In the perovskite material system, three-dimensional perovskite materials (such as MAPbI3 and FAPbI3) are currently the most widely used absorption layer materials in perovskite solar cells. Three-dimensional perovskite materials have efficient light absorption ability, good carrier mobility and long carrier diffusion length, which enable them to exhibit excellent performance in high-efficiency photovoltaic devices. However, three-dimensional perovskite materials are highly sensitive to the environment, and their crystal structure is easily decomposed under the action of moisture and heat, resulting in poor stability of the device. In addition, defect recombination is easily generated at the interface, further limiting the improvement of its photoelectric conversion efficiency.
[0004] In contrast, two-dimensional perovskite materials (such as (PEA)2PbI4) exhibit significant advantages due to their layered structure. The organic cation layer in the two-dimensional perovskite has hydrophobicity and steric hindrance effects, which can effectively block the intrusion of moisture and oxygen, thereby significantly improving the moisture resistance and oxidation resistance of the device. In addition, the low defect density of the two-dimensional perovskite material can effectively reduce the interface non-radiative recombination loss, and its smooth surface also helps to optimize the interface charge transfer efficiency. However, the carrier transport capacity of the two-dimensional perovskite material is low, mainly because the organic cation layer in its layered structure forms a barrier to the migration of electrons and holes in the vertical direction. At the same time, its band gap is wide (usually greater than 2 eV), and the absorption range of the solar spectrum is narrow, especially the absorption of visible light and near-infrared light is weak, which seriously limits its photoelectric conversion efficiency.
[0005] In order to combine the advantages of two-dimensional and three-dimensional perovskite materials, two-dimensional / three-dimensional composite perovskite absorption layers have become a research hotspot in recent years. The two-dimensional / three-dimensional composite structure can significantly reduce the interface defect density and enhance the moisture resistance and heat resistance of the device by covering a layer of two-dimensional perovskite material on the electron transport layer to provide interface passivation and protection. On this basis, the deposition of a three-dimensional perovskite material layer as the main absorption layer can effectively make up for the problem of insufficient light absorption capacity of two-dimensional perovskite. The two-dimensional / three-dimensional composite structure can not only take advantage of the stability of two-dimensional perovskite, but also optimize the carrier transmission path by constructing a gradient energy level structure, significantly improving the photoelectric performance. At the same time, the two-dimensional perovskite layer can be used as a template to promote the vertical orientation growth of three-dimensional perovskite crystals and further improve the carrier transmission efficiency. However, the inconsistent crystal orientation between the two-dimensional perovskite material layer and the three-dimensional perovskite material layer hinders carrier transmission and cannot give full play to the advantages of two-dimensional / three-dimensional composite perovskite solar cells. Summary of the invention
[0006] In order to solve the above problems, the present invention provides a two-dimensional perovskite vertically oriented growth solar cell, including a substrate layer, an electron transport layer, a perovskite absorption layer, a hole transport layer, and a metal top electrode layer arranged in sequence from bottom to top. Among them, the electron transport layer includes a tin dioxide film and tin dioxide nanoparticles, and the tin dioxide nanoparticles are placed on the tin dioxide film on one side of the perovskite absorption layer. The perovskite absorption layer includes a two-dimensional perovskite material layer and a three-dimensional perovskite material layer, the two-dimensional perovskite material layer is in contact with the tin dioxide nanoparticles, and the three-dimensional perovskite material layer is in contact with the hole transport layer.
[0007] The present invention realizes vertically oriented crystal growth through the rough surface of tin dioxide nanoparticles, two-dimensional perovskite material layer and three-dimensional perovskite material layer. This vertically oriented structure reduces the existence of grain boundaries, increases the diffusion length and migration efficiency of carriers, and thus improves the photoelectric conversion efficiency.
[0008] Furthermore, the thickness of the tin dioxide film is 30-50 nanometers, and the particle size of the tin dioxide nanoparticles is 5-20 nanometers.
[0009] Furthermore, the tin dioxide nanoparticles are partially embedded in the tin dioxide film. The structure of the tin dioxide film partially embedded in the tin dioxide nanoparticles enhances the bonding force between the nanoparticles and the film. This strong bond significantly improves the long-term stability of the electron transport layer and the durability of the perovskite solar cell. In addition, this embedded design shortens the electron transmission path between the tin dioxide nanoparticles and the tin dioxide film, reduces the resistance loss at the interface, and thus improves the efficiency of electron transmission from the nanoparticles to the film. In addition, the surface of the partially embedded tin dioxide nanoparticles is still exposed under the perovskite material layer, and its raised particle structure can enhance the scattering and light trapping effects of light, thereby increasing the utilization of light by the perovskite absorption layer and further improving the photoelectric conversion efficiency.
[0010] Furthermore, the material of the substrate layer is ITO or FTO, the material of the hole transport layer is Spiro-OMeTAD, and the material of the metal top electrode layer is gold.
[0011] Furthermore, the tin dioxide nanoparticles are doped with zinc oxide nanoparticles. The doped zinc oxide (ZnO) nanoparticles can effectively guide the two-dimensional perovskite crystals to grow preferentially along the vertical direction by optimizing the surface roughness, providing high-energy nucleation sites, and improving the interface lattice matching.
[0012] On the other hand, the present invention provides a method for preparing a two-dimensional perovskite vertically oriented growth solar cell, comprising the following steps: Step 1, preparing a tin dioxide film on a substrate layer; Step 2, disposing tin dioxide nanoparticles on the tin dioxide film; Step 3, preparing a two-dimensional perovskite material layer on the tin dioxide nanoparticles; Step 4, preparing a three-dimensional perovskite material layer on the two-dimensional perovskite material layer; Step 5, preparing a hole transport layer on the three-dimensional perovskite material layer; Step 6: Prepare a metal top electrode layer on the hole transport layer.
[0013] Furthermore, in step 1, a tin dioxide thin film is prepared on the ITO by using a spin coating method.
[0014] Furthermore, in step 2, the tin dioxide nanoparticles are spin-coated on the tin dioxide film using a spin-coating method.
[0015] Furthermore, in step 3, the precursor solution of the two-dimensional perovskite material is spin-coated on the surface of the tin dioxide nanoparticles, and the two-dimensional perovskite material layer is obtained after annealing.
[0016] Furthermore, in step 4, a precursor solution of the three-dimensional perovskite material is spin-coated on the surface of the two-dimensional perovskite material layer, and the three-dimensional perovskite material layer is obtained after annealing.
[0017] Beneficial effects of the present invention: The present invention promotes the vertically oriented growth of two-dimensional perovskite and three-dimensional perovskite through the rough surface of tin dioxide nanoparticles, thereby forming a highly ordered crystal structure. This vertically oriented perovskite crystal significantly reduces the number of grain boundaries, reduces carrier scattering and recombination losses between grains, and improves the diffusion length and migration efficiency of carriers. In addition, the partially embedded tin dioxide nanoparticle protrusion structure can also enhance the scattering and light trapping effects of light, improve the utilization rate of light by the perovskite absorption layer, and thus effectively improve the photoelectric conversion efficiency.
[0018] The present invention enhances the bonding force between the nanoparticles and the film by designing a structure in which the tin dioxide nanoparticles are partially embedded in the tin dioxide film. This strong bonding effectively prevents the nanoparticles from falling off due to mechanical stress or environmental factors (such as thermal stress) during long-term use, thereby significantly improving the mechanical stability and durability of the electron transport layer. In addition, the two-dimensional perovskite layer has excellent moisture resistance and oxidation resistance, and after combining with the three-dimensional perovskite, the overall environmental stability of the device is further enhanced, so that the device can still maintain high photoelectric performance in complex environments such as humidity and high temperature.
[0019] The present invention adopts a spin coating method to prepare an electron transport layer, a two-dimensional perovskite layer and a three-dimensional perovskite layer, which has a simple process, low cost and is easy to control. The spin coating process is not only suitable for laboratory research, but also has good process compatibility and is suitable for industrial large-scale production. In addition, the combination of tin dioxide film and embedded tin dioxide nanoparticles does not require complicated processing steps, further reducing the difficulty of production, and laying the foundation for the commercial application of high-efficiency perovskite solar cells.
[0020] Based on the above beneficial effects, the present invention has good application prospects in the field of perovskite solar cell technology. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 Schematic diagram of a solar cell with vertically oriented growth of two-dimensional perovskite.
[0022] In the figure: 1. Base layer; 2. Electron transport layer; 3. Perovskite absorption layer; 4. Hole transport layer; 5. Metal top electrode layer. DETAILED DESCRIPTION
[0023] In order to make the objectives, technical solutions and advantages of the present application more clearly understood, the present application is further described in detail below with reference to the accompanying drawings and examples.
[0024] Example 1 The present invention provides a two-dimensional perovskite vertically oriented growth solar cell, such as Figure 1 As shown, it includes a base layer 1, an electron transport layer 2, a perovskite absorption layer 3, a hole transport layer 4, and a metal top electrode layer 5.
[0025] Among them, the base layer 1 uses ITO or FTO transparent conductive glass (thickness is about 1.1 mm), which has good conductivity and allows light to enter the perovskite absorption layer, providing mechanical support and bottom electrode function for photovoltaic devices. The electron transport layer 2 is composed of a tin dioxide film and tin dioxide nanoparticles partially embedded in the tin dioxide film, wherein the thickness of the tin dioxide film is 30-50 nanometers, which is used to provide a continuous and uniform electron transmission path, and the particle size of the tin dioxide nanoparticles is 5-20 nanometers, which are partially embedded in the film to enhance the bonding force between the particles and the film. At the same time, the exposed particle structure increases the roughness of the surface of the electron transport layer, providing a template for the vertical orientation growth of the perovskite crystal. The perovskite absorption layer 3 includes a two-dimensional perovskite material layer and a three-dimensional perovskite material layer. The two-dimensional perovskite material layer is (PEA)2PbI4; the three-dimensional perovskite material layer is MAPbI3. The two-dimensional perovskite material layer is in direct contact with the tin dioxide nanoparticles, and the vertically oriented crystal structure improves the diffusion length and migration efficiency of the carriers. The three-dimensional perovskite material layer is located on the two-dimensional perovskite material layer and is in contact with the hole transport layer, providing efficient light absorption and charge separation capabilities for solar cells. The hole transport layer 4 uses Spiro-OMeTAD material (thickness is about 50-100 nanometers), which is used to selectively transmit photogenerated holes and block the injection of electrons into the perovskite layer, thereby reducing recombination losses. The top layer is a metal top electrode layer 5, made of gold (Au), with a thickness of 50-100 nanometers, which is used to collect holes and conduct current. The overall structure not only improves the photoelectric conversion efficiency through the organic combination of various functional layers, but also significantly improves the long-term stability and environmental tolerance of the device.
[0026] In the present invention, the vertically oriented structure of the two-dimensional perovskite makes the inorganic [PbI6] 4-The octahedra are arranged in an orderly manner along the vertical direction (c-axis direction), forming a continuous carrier transport channel that runs through the entire perovskite film. This orderly stacking of inorganic layers significantly reduces the number of grain boundaries, which are often the main locations for scattering and recombination during carrier transport. By reducing the grain boundaries, the probability of carrier scattering and recombination in the vertical direction is greatly reduced, thereby improving the transport efficiency and diffusion length. Secondly, the inorganic layer of the two-dimensional perovskite is the main channel for carrier transport, while the organic cation layer (such as phenylethylamine cation PEA⁺) will hinder the lateral carrier transport due to its low conductivity. In the randomly oriented two-dimensional perovskite, the carriers have to cross the obstruction of the interlayer organic layer, resulting in a decrease in the transport efficiency. The vertically oriented structure avoids this problem. The arrangement direction of the inorganic layer is consistent with the carrier migration path, thereby providing a low-resistance transmission channel and significantly optimizing the carrier migration efficiency. At the same time, the vertically oriented growth also reduces the interlayer impedance in the two-dimensional perovskite layer. Through the orderly arrangement in the vertical direction, the interlayer distance inside the crystal is more uniform and compact, thereby reducing the interlayer resistance. At the same time, the vertically oriented structure improves the interface bonding quality between the perovskite layer and the tin dioxide electron transport layer and the three-dimensional perovskite layer. This optimized interface reduces the barrier for charge injection and extraction, and further improves the efficiency of carrier transfer from the two-dimensional perovskite layer to other functional layers. In addition, more importantly, the vertically oriented two-dimensional perovskite layer provides an ordered template for the growth of subsequent three-dimensional perovskite material layers. Under the guidance of the two-dimensional perovskite material layer, the three-dimensional perovskite material layer also achieves orderly growth in the vertical direction, so that the entire perovskite absorption layer 3 has a continuous crystal orientation. This structure not only improves the coupling efficiency between the two-dimensional and three-dimensional perovskite layers, but also optimizes the migration path of carriers in the entire absorption layer, thereby further improving the photoelectric conversion efficiency of the solar cell.
[0027] Example 2 The present invention provides a method for preparing a two-dimensional perovskite vertically oriented growth solar cell, comprising the following steps: Step 1: Prepare a tin dioxide film on the substrate layer 1. Specifically, an ITO glass with a size of 25 mm × 25 mm is selected as the substrate. The substrate is first ultrasonically cleaned by acetone, isopropanol and deionized water for 10 minutes respectively, and treated with a plasma cleaner for 5 minutes to remove surface contamination and enhance hydrophilicity. Then, a 0.1 M tin dioxide (SnO2) precursor solution is prepared, SnCl4·5H2O is dissolved in isopropanol, and after being fully stirred, it is coated on the ITO glass surface by spin coating (3000 rpm, 30 seconds), and then annealed at 150 °C for 30 minutes to form a uniform tin dioxide film with a thickness of 30-50 nm.
[0028] Step 2: Arrange tin dioxide nanoparticles on the tin dioxide film. Specifically, prepare a tin dioxide nanoparticle solution with a particle size of 10 nanometers. Disperse the tin dioxide nanoparticles in an isopropanol solvent (concentration of 5 wt%) and uniformly disperse them by ultrasonic stirring for 30 minutes. Subsequently, the nanoparticle solution is coated on the annealed tin dioxide film by spin coating (3000 rpm, 30 seconds) to form an embedded structure in which some nanoparticles are embedded in the surface of the film. Finally, anneal the sample at 150 °C for 15 minutes to stabilize the distribution of the nanoparticles and enhance their bonding with the film.
[0029] Step 3: Prepare a two-dimensional perovskite material layer on tin dioxide nanoparticles. Specifically, a precursor solution of phenylethylamine iodide (PEAI) and lead iodide (PbI2) mixed in a 2:1 molar ratio was prepared and dissolved in a DMF:DMSO mixed solvent with a volume ratio of 4:1. The solution concentration was 0.5 M. The solution was stirred at 60 °C for 2 hours until it was completely dissolved. The precursor solution was drop-coated on the surface of the tin dioxide nanoparticles, and after uniform film formation by spin coating (2000 rpm, 30 seconds), it was annealed at 100 °C for 10 minutes to finally form a (PEA)2PbI4 two-dimensional perovskite material layer with a thickness of 10-20 nanometers. Its vertically oriented crystal structure significantly optimizes the carrier transmission path.
[0030] Step 4: Prepare a three-dimensional perovskite material layer on the two-dimensional perovskite material layer. Specifically, methylamine iodide (MAI) and lead iodide (PbI2) are mixed in a 1:1 molar ratio, dissolved in a DMF:DMSO mixed solvent with a volume ratio of 4:1, and a three-dimensional perovskite precursor solution with a concentration of 1.2 M is prepared, and stirred at 60 °C for 1 hour to ensure complete dissolution. The precursor solution is drop-coated on the surface of the two-dimensional perovskite material layer, and a thin film is deposited by spin coating (4000 rpm, 30 seconds), and an anti-solvent (such as toluene) is added to promote crystal nucleation and growth. After that, the sample is annealed at 120 °C for 15 minutes, and finally a MAPbI3 three-dimensional perovskite material layer with a thickness of 400-700 nanometers is formed, whose crystal growth is vertically ordered and well combined with the two-dimensional layer.
[0031] Step 5, prepare a hole transport layer 4 on the three-dimensional perovskite material layer. Specifically, when preparing the hole transport layer 4, first prepare a Spiro-OMeTAD solution, dissolve 72.3 mg Spiro-OMeTAD in 1 ml chlorobenzene solvent, add 17.5µl Li-TFSI solution (520 mg Li-TFSI dissolved in 1 ml acetonitrile) and 28.8 µl tri-tert-butyl phosphate (TBP) as additives, and stir well. Subsequently, the solution is drop-coated on the surface of the three-dimensional perovskite material layer, and a uniform hole transport layer 4 with a thickness of 50-100 nanometers is deposited by spin coating (3000rpm, 30 seconds).
[0032] Step 6: Prepare a metal top electrode layer 5 on the hole transport layer 4. Specifically, a metal top electrode is deposited on the surface of the hole transport layer by a thermal evaporation process. Pure gold (Au) is used as the metal material, and a 50-100 nanometer thick gold electrode is uniformly deposited on the hole transport layer 4 by a thermal evaporation device under high vacuum conditions to ensure good contact between the electrode and the hole transport layer 4 and charge collection capability.
[0033] In this application, the rough surface of the tin dioxide nanoparticles provides a large number of high-energy sites, which promotes the initial nucleation of the two-dimensional perovskite crystals and guides the crystals to grow in the vertical direction to minimize the surface free energy. In addition, the interface lattice matching and chemical bonding between the tin dioxide nanoparticles and the perovskite material (such as the interaction between oxygen vacancies and Pb²⁺, I⁻) further stabilize the vertically oriented growth path. At the same time, the bulky organic cations (such as PEA⁺) in the two-dimensional perovskite material are more inclined to stack in layers on the inorganic [PbI6] due to their steric hindrance effect. 4- The side of the octahedral layer promotes the stacking of the inorganic layer in the vertical direction. In addition, during the spin coating and annealing process, the dynamic effect of solvent distribution and volatilization on the rough surface also contributes to the rapid growth of vertical crystals, while the annealing process further optimizes the order of the vertical orientation through crystal rearrangement and stress release. Ultimately, this vertically oriented crystal structure can effectively reduce the number of grain boundaries and improve the carrier migration efficiency and photoelectric conversion performance.
[0034] Preferably, after spin coating the tin dioxide nanoparticles, ultrasonic vibration substrate layer 1 is used during annealing, and mechanical disturbance is applied to the nanoparticles through acoustic vibration, thereby improving the microstructure and interface characteristics of the film, thereby improving the overall performance of the perovskite solar cell. Specifically, ultrasonic vibration helps to rearrange the tin dioxide nanoparticles during annealing, increase the density between particles and reduce the pores and defects in the film, thereby forming a more uniform and continuous electron transmission channel. This density optimization reduces the resistance and interface state density of the film, and improves the extraction efficiency and mobility of carriers. In addition, ultrasonic vibration can also release stress between particles, prevent cracks or particle peeling during thermal annealing, and further enhance the mechanical stability and long-term durability of the film. The surface micro-disturbance caused by ultrasonic vibration can also optimize the surface roughness of the film, provide more uniform nucleation sites for subsequent two-dimensional perovskite materials, thereby promoting its vertically oriented crystal growth and improving the crystal quality of the perovskite absorption layer. This process combines the dual advantages of thermal treatment and acoustic perturbation, which not only improves the conductivity and photoelectric conversion efficiency of the tin dioxide electron transport layer 2, but also reduces the interface recombination loss.
[0035] The present invention also includes an ultrasonic vibration device, which specifically includes an ultrasonic vibration table, a substrate fixing fixture and a temperature control system. The ultrasonic vibration table serves as the main vibration source, generates high-frequency vibrations through a built-in ultrasonic generator, and transmits the vibration energy to a substrate layer fixed to the surface of the vibration table. The substrate is fixed to the vibration table by a fixture or vacuum adsorption to ensure the stability of the substrate position during the vibration process. The device is also equipped with a controllable heating system to provide the required heat treatment temperature (such as 100-150 ° C) during the annealing process and simultaneously apply ultrasonic vibrations. The vibration frequency (such as 20-50 kHz) and amplitude are adjustable to meet the needs of different materials and film structures. Through this design, the ultrasonic vibration during annealing can act evenly on the substrate and film surface, promoting the rearrangement, densification and stress release of nanoparticles.
[0036] Preferably, the direction of ultrasonic vibration is consistent with the surface normal direction of the substrate layer 1. Vertical vibration promotes the rearrangement and tighter stacking of nanoparticles along the normal direction of the substrate by applying an upward mechanical impact force to the film. Compared with vibrations in other directions, vertical vibration can more effectively fill the gaps and holes inside the film, thereby forming a more dense electron transport layer. This dense structure reduces the resistance in the carrier transmission path and improves the efficiency of electron migration. In addition, vertical vibration helps to form a rough structure with microscopic undulations on the surface of the film. This surface roughness provides more high-energy sites for the nucleation and vertical orientation growth of perovskite crystals, which helps to optimize the crystal quality and growth direction of the perovskite layer, thereby reducing grain boundary defects and improving the photoelectric conversion efficiency.
[0037] Example 3 On the basis of Example 1 and Example 2, zinc oxide nanoparticles with a particle size of 10-20 nm are doped into tin dioxide nanoparticles to promote the vertical orientation growth of two-dimensional perovskite materials. The specific method is to disperse tin dioxide and zinc oxide nanoparticles in isopropanol respectively, and mix them in a mass ratio of 10:1 (zinc oxide accounts for 10 wt%) after ultrasonic stirring to form a uniform SnO2-ZnO mixed nanoparticle solution. The mixed solution is then drop-coated on a cleaned ITO substrate, and a mixed nanoparticle layer is formed by spin coating (3000 rpm, 30 seconds), and annealed at 150 °C for 15 minutes to ensure stable attachment and partial embedding of the particles. The surface roughness and high-energy nucleation sites of the mixed nanoparticle layer are significantly improved by the doped zinc oxide, and at the same time, ZnO and [PbI6] 4- The lattice matching of the octahedron helps guide the orderly growth of two-dimensional perovskite crystals in the vertical direction. Then, the precursor solution of phenylethylamine iodide (PEAI) and lead iodide (PbI2) was drop-coated on the surface of the SnO2-ZnO mixed layer, and the film was spin-coated and annealed at 100 °C for 10 minutes to generate a vertically oriented two-dimensional perovskite material layer ((PEA)2PbI4). The doping of zinc oxide nanoparticles not only promotes the vertical growth of perovskite materials by optimizing the roughness, interface chemistry and lattice compatibility of the electron transport layer, but also improves the carrier transport performance and photoelectric conversion efficiency, providing a new approach for high-efficiency perovskite solar cells.
[0038] Preferably, the electron transport layer 2 is designed to include a double-layer nanoparticle structure, with large-diameter tin dioxide nanoparticles (diameter 20-30 nm) used in the lower layer to increase the surface roughness and nucleation site density, and small-diameter zinc oxide nanoparticles (diameter 5-10 nm) covered in the upper layer to further passivate the interface and optimize the crystal nucleation environment, which can significantly improve the performance of perovskite solar cells. Among them, the large-diameter tin dioxide particles provide more high-energy sites for the vertical orientation growth of perovskite crystals by increasing the roughness, while the small-diameter zinc oxide particles have good lattice matching and passivation, which can reduce the interface defect density, reduce the recombination of carriers at the interface, and optimize the crystal growth environment, further improving the quality of perovskite crystals and photoelectric conversion efficiency. The specific preparation method is as follows: first, tin dioxide nanoparticles with a particle size of 20-30 nm are dispersed in isopropanol (concentration of 5 wt%), and are evenly coated on the surface of the cleaned ITO substrate by spin coating (3000 rpm, 30 seconds), and annealed at 150 °C for 15 minutes to form a lower layer structure; then, zinc oxide nanoparticles with a particle size of 5-10 nm are dispersed in isopropanol (concentration of 2 wt%), and deposited on the tin dioxide layer by the same spin coating method, and annealed at 150 °C for 10 minutes to form an upper layer structure. Through this double-layer design, the electron transport layer not only has stronger conductivity and better interface quality, but also provides a more ideal foundation for the vertical orientation growth of two-dimensional perovskite materials and subsequent carrier transport.
[0039] In summary, the present invention provides a two-dimensional perovskite vertically oriented growth solar cell and a preparation method thereof, which improves the photoelectric conversion efficiency and device stability of the perovskite solar cell by optimizing the design of the electron transport layer 2 and the perovskite absorption layer 3, and lays a foundation for further realizing efficient, stable and large-scale perovskite photovoltaic devices. At the same time, this design concept has certain guiding significance for the research on crystal growth, interface regulation and functionalized electron transport layer of the perovskite material system.
[0040] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application shall be included in the scope of protection of the present application.
Claims
1. A two-dimensional perovskite vertically oriented growth solar cell, comprising a substrate layer, an electron transport layer, a perovskite absorption layer, a hole transport layer, and a metal top electrode layer arranged in sequence from bottom to top, characterized in that: The electron transport layer includes a tin dioxide film and tin dioxide nanoparticles, the tin dioxide nanoparticles are placed on the tin dioxide film on one side of the perovskite absorption layer, the perovskite absorption layer includes a two-dimensional perovskite material layer and a three-dimensional perovskite material layer, the two-dimensional perovskite material layer is in contact with the tin dioxide nanoparticles, and the three-dimensional perovskite material layer is in contact with the hole transport layer.
2. The two-dimensional perovskite vertically oriented growth solar cell according to claim 1, characterized in that: The thickness of the tin dioxide film is 30-50 nanometers, and the particle size of the tin dioxide nanoparticles is 5-20 nanometers.
3. The two-dimensional perovskite vertically oriented growth solar cell according to claim 2, characterized in that: The tin dioxide nanoparticles are partially embedded in the tin dioxide thin film.
4. The two-dimensional perovskite vertically oriented growth solar cell according to claim 1, characterized in that: The material of the substrate layer is ITO or FTO, the material of the hole transport layer is Spiro-OMeTAD, and the material of the metal top electrode layer is gold.
5. The two-dimensional perovskite vertically oriented growth solar cell according to claim 1, characterized in that: The tin dioxide nanoparticles are doped with zinc oxide nanoparticles.
6. A method for preparing a two-dimensional perovskite vertically oriented growth solar cell, characterized in that: The steps include: Step 1, preparing a tin dioxide film on a substrate layer; Step 2, disposing tin dioxide nanoparticles on the tin dioxide film; Step 3, preparing a two-dimensional perovskite material layer on the tin dioxide nanoparticles; Step 4, preparing a three-dimensional perovskite material layer on the two-dimensional perovskite material layer; Step 5, preparing a hole transport layer on the three-dimensional perovskite material layer; Step 6: Prepare a metal top electrode layer on the hole transport layer.
7. The method for preparing a two-dimensional perovskite vertically oriented growth solar cell according to claim 6, characterized in that: In step 1, a tin dioxide thin film is prepared on ITO by a spin coating method.
8. The method for preparing a two-dimensional perovskite vertically oriented growth solar cell according to claim 7, characterized in that: In step 2, the tin dioxide nanoparticles are spin-coated on the tin dioxide film using a spin-coating method.
9. The method for preparing a two-dimensional perovskite vertically oriented growth solar cell according to claim 8, characterized in that: In step 3, a precursor solution of the two-dimensional perovskite material is spin-coated on the surface of the tin dioxide nanoparticles, and a two-dimensional perovskite material layer is obtained after annealing.
10. The method for preparing a two-dimensional perovskite vertically oriented growth solar cell according to claim 9, characterized in that: In step 4, a precursor solution of the three-dimensional perovskite material is spin-coated on the surface of the two-dimensional perovskite material layer, and the three-dimensional perovskite material layer is obtained after annealing.
Citation Information
Patent Citations
Double-layer electron transport layer, perovskite solar cell with double-layer electron transport layer, preparation method of perovskite solar cell and application of perovskite solar cell
CN115020596A